DEVELOPING CRITICAL THINKING SKILLS FOR UNIVERSITY SUCCESS IN THE AGE OF DIGITAL TECHNOLOGY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article deals with the problem that the modern world labor market again challenges education: familiar professions are losing relevance, while specialists with developed systems thinking, which is impossible without creativity and the ability to critically evaluate information, are becoming very popular, and developed soft skills are even valued. more than professional skills. It is also analyzed that the degree of formation of critical thinking in any situation depends on personal and social success, including the competitiveness of the future specialist in the professional field. At the same time, much attention is paid to the methods and advice of the famous British scientist Tom Chatfield about how to improve the understanding of digital technologies and their use in education. It has been established that the preparation of good professionals in schools, universities and companies, as well as the use and creation of online courses for both academic institutions and businesses for success in the 21st century, depends on well-developed critical thinking skills.